2012
DOI: 10.1152/japplphysiol.00100.2012
|View full text |Cite
|
Sign up to set email alerts
|

The startle response during whiplash: a protective or harmful response?

Abstract: Whiplash injuries are common following rear-end collisions. During such collisions, initially relaxed occupants exhibit brisk, stereotypical muscle responses consisting of postural and startle responses that may contribute to the injury. Using prestimulus inhibition, we sought to determine if the startle response elicited during a rear-end collision contributes to head stabilization or represents a potentially harmful overreaction of the body. Three experiments were performed. In the first two experiments, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This was because the optimal neural processing time constants, obtained from the optimization simulations for APF and MLF, were different. A wide range of muscle onset delays was observed in various volunteer studies as summarized by Mang et al (2012) and Siegmund et.al (2002) therefore, it might be worthy to investigate further regarding how it affects the head motion during rear impact collision. The APF controller exhibited the best performance based on the historic data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This was because the optimal neural processing time constants, obtained from the optimization simulations for APF and MLF, were different. A wide range of muscle onset delays was observed in various volunteer studies as summarized by Mang et al (2012) and Siegmund et.al (2002) therefore, it might be worthy to investigate further regarding how it affects the head motion during rear impact collision. The APF controller exhibited the best performance based on the historic data.…”
Section: Discussionmentioning
confidence: 96%
“…To further study the effects of muscle contractions on whiplash injuries, activation time and force time histories for the cervical muscles should be considered (Siegmund et al 2002). Data from the literature as summarized by Mang et al (2012) have shown that the activation of cervical muscles occurs about 50-100ms after the onset of vehicle acceleration. This muscle response is considered to occur early enough in a rear impact event to alter the head and neck kinematics and affect the risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Different efforts have been also made to associate posture and muscular activation patterns. [ 33 , 34 ] Functionally, neck muscles can be divided into superficial and deep muscles. Superficial muscles, such as the sternocleidomastoid, that we analyzed in our study, are engaged during wide movements.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize such effects, 15–20 minutes were allotted between two successive EXT trial blocks and comparisons between them showed no differences in neck and arm muscle FTR amplitudes indicating no habituation carryover effects between conditions with this rest interval. [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Freefall onset occurred without warning in EXT trials, and was determined by participants who initiated it at a self-selected time once the signal for the trial was given during SLF trials. To minimize habituation participants received no practice trials, and twenty minutes were allotted between the end of EXT trials and the start of SLF trials [16]. To evaluate the effectiveness of the washout interval in minimizing possible order effects, a different cohort of five (one female) untested participants (age 23.6 ± 2.51 years) received sequential EXT trial blocks with a 20 minute seated rest period between them..…”
Section: Participants and Methodsmentioning
confidence: 99%